(untitled) (Journal of Nobel Medical College, 2022)
Background: Penetrating keratoplasty is commonly performed surgery in patients suffering from corneal blindness and visual impairment, where full thickness diseased cornea is replaced with healthy cornea. This study aims to outline indications of Penetrating keratoplasty and visual outcomes following the procedure. Materials and Methods: This retrospective, hospital-based study included 48 eyes of 48 subjects fulfilling inclusion criteria and underwent Penetrating keratoplasty from January 2017-2020 at Bharatpur Eye Hospital. General ophthalmologic examination was done preoperatively and postoperatively. Indication of the surgery along with demographic outline and requisite investigations were performed. Results: Mean age of the subjects was 47±1.83 years (13-74 years) where most of them were in 61-70years (23%) age group. Male subjects were more (62.5%) compared to females. Triple procedure was performed in 6.25 percent of patients. The most common indication was infective keratitis (52%) followed by corneal opacity/ scarring, regrafts, keratoconus and bullous keratopathy. Penetrating keratoplasty was performed slightly more for therapeutic purpose (52%) than optical. Intraoperative complications were observed in 16.7% of patients, positive vitreous pressure being the sole cause. Ameliorated visual acuity was observed in 71% of patients with43.75% of patients having VA of ≥3/60 Conclusion: Infective keratitis was the predominant indication followed by corneal opacity/ scarring. Penetrating keratoplasty helps in maintaining integrity of the globe along with restoration of vision